A COMPARATIVE STUDY OF THE ARCHITECTURES AND APPLICATIONS OF SCALABLE HIGH-PERFORMANCE DISTRIBUTED FILE SYSTEMS - Dada, E. G.; Joseph, S. B. (FUDMA JOURNAL OF SCIENCES, 2023)
Distributed File Systems have enabled the efficient and scalable sharing of data across networks. These systems were designed to handle some technical problems associated with network data. For instance reliability and availability of data, scalability of infrastructure supporting storage, high cost of gaining access to data, maintenance cost and expansion. In this paper, we attempt to make a comparison of the key technical blocks that are referred to as the mainstay of Distributed File Systems such as Hadoop FS, Google FS, Luster FS, Ceph FS, Gluster FS, Oracle Cluster FS and TidyFS. This paper aims at elucidating the basic concepts and techniques employed in the above mentioned File Systems. We explained the different architectures and applications of these Distributed File Systems
Keywords: Distributed File Systems, Google File System, Hadoop File System, Oracle Cluster File System, Ceph File System